The Trio attribute as a functional feature in varioustext Mining Computational Approaches - Dr. Tareef Kamil Mustafa (International Journal of Advanced Science and Technology, 2020)
Word Attributesarethe main features that are used as a token in deferent text mining approaches, while the trio attribute is defined simply as a “three-word linguistic sentence”.This research is concerned in using the trio attribute as the main feature instead of the regular widely used “single word” or even “pair of words” in the latest computational approaches projects. The authorship detection subject has been chosen to prove the efficiency and the consistency of the trio as the most functional feature among others.